Labor and Monopoly Capital : The Degradation of Work in the Twentieth Century - Braverman, Harry (Book collections on Project MUSE., 1998)
This widely acclaimed book, first published in 1974, was a classic from its first day in print. Written in a direct, inviting way by Harry Braverman, whose years as an industrial worker gave him rich personal insight into work, Labor and Monopoly Capital overturned the reigning ideologies of academic sociology. This new edition features an introduction by John Bellamy Foster that sets the work in historical and theoretical context, as well as two rare articles by Braverman, ""The Degradation of Work in the Twentieth Century"" (1975) and ""Two Comments"" (1976), that add much to our understandi.